2021
DOI: 10.1088/1755-1315/841/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Mixed Expansive Soil and Additive Minerals as Subgrade Layer

Abstract: South Sulawesi is one of eastern Indonesia area covered with coastal line which have growth fast of industries. Infrastructure builds and developed in a row of industries population. Most coastal are lowland areas with expansive soil as primary soil forms. Exhaustive laboratory test conducts for clay taken from lowland area in south Sulawesi and lime up to 10% and volcanic up to 25% as stabilizers to know the Physical-mechanical properties and mineralogical when the expansive soil stabilized. The extensive soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…They found that lime and artificial pozzolana greatly improve the engineering characteristics of BCS. F Sitepu et al [20] investigated the engineering characteristics of VA stabilized BCS by means of the Atterberg limit, CBR and UCS and found that VA increased UCS and CBR, and decreased the liquid limit (LL) and plasticity index (PI), but not significantly. A combination of lime and VA presented a better improvement.…”
Section: Introductionmentioning
confidence: 99%
“…They found that lime and artificial pozzolana greatly improve the engineering characteristics of BCS. F Sitepu et al [20] investigated the engineering characteristics of VA stabilized BCS by means of the Atterberg limit, CBR and UCS and found that VA increased UCS and CBR, and decreased the liquid limit (LL) and plasticity index (PI), but not significantly. A combination of lime and VA presented a better improvement.…”
Section: Introductionmentioning
confidence: 99%